Metaphor as a methodological tool: identifying teachers' social justice dispositions across diverse secondary school settings. Issue 6 (18th August 2017) - Mills, Carmen; Molla, Tebeje; Gale, Trevor; Cross, Russell; Parker, Stephen; Smith, Catherine
Abstract: This article investigates the social justice dispositions of teachers and principals in secondary schools as inferred from their metaphoric expressions. Drawing on a Bourdieuian account of disposition, our focus is the use of metaphor as a methodological tool to identify and reveal these otherwise latent forces within our data. Our analysis shows evidence of redistributive, recognitive and activist conceptions of social justice. We argue that these three social justice dispositions may be insufficient to meaningfully address persisting inequalities in the school system and that a capability-based social justice disposition – absent in our data – is needed. We conclude by highlighting that: social justice dispositions can change; a valid interpretation of metaphors requires 'contextual stabilization'; and metaphors for social justice are differently constructed in different contexts, influenced by the different social, cultural and material conditions of schools.